Tell Me Something I Don't Already Know: Learning in Low‐ and High‐Inflation Settings - Weber, Michael; Candia, Bernardo; Afrouzi, Hassan; Ropele, Tiziano; Lluberas, Rodrigo; Frache, Serafin; Meyer, Brent; Kumar, Saten; Gorodnichenko, Yuriy; Georgarakos, Dimitris; Coibion, Olivier; Kenny, Geoff; et al. (Econometrica, 2025)
Using randomized control trials (RCTs) applied over time in different countries, we study whether the economic environment affects how agents learn from new information. We show that as inflation rose in advanced economies, both households and firms became more attentive and informed about publicly available news about inflation, leading them to respond less to exogenously provided information about inflation and monetary policy. We also study the effects of RCTs in countries where inflation has been consistently high (Uruguay) and low (New Zealand) as well as what happens when the same agents are repeatedly provided information in both low‐ and high‐inflation environments (Italy). Our results broadly support models in which inattention is an endogenous outcome that depends on the economic environment.